Mechanism of Poria cocos Polysaccharide Regulating Autophagy and Chemotherapy Resistance of Hepatocellular Carcinoma Cells through LncRNAHCG11/miR-539-3p 539-3p - Yongfang CHEN; Yanke LI; Shujing ZHANG (Shipin gongye ke-ji)
Objective: To explore the effects and mechanism of Poria cocos polysaccharide (PCP) on proliferation, autophagy and chemotherapy resistance of hepatocellular carcinoma cells. Methods: HepG-2/DDP cells in logarithmic phase were randomly divided into control group, PCP group (7.5, 15, 30 μg/mL PCP), shNC group, HCG11 siRNA group (transfection of 50 nmol/L HCG1 interference sequence), pcDNA group (transfection of 2 μg pcDNA), pcDNA3.1-HCG11 group (transfection of 2 μg pcDNA3.1-HCG11), PCP group (30 μg/mL PCP) and PCP+pcDNA3.1-HCG11 group (transfection of 2 μg pcDNA3.1-HCG11+30 μg/mL PCP). MTT assay was used to detect the drug resistance and inhibition rate of hepatocellular carcinoma cells, western blot was used to detect the levels of Beclin-1, LC3, and quantitative real time polymerase chain reaction (qRT-PCR) was used to detect the levels of LncRNA HCG11 and miR-539-3p in the cell lines. Double luciferase report experiment was used to detect the targeting relationship between LncRNA HCG11 and miR-539-3p, and nude mice tumorigenesis experiment was used to verify the influence of tumor weight, tumor volume and autophagy-related protein level in nude mice. Results: 4~128 µg/mL PCP had a certain inhibitory effect on HepG-2/DDP cells. PCP of 7.5, 15, 30 μg/mL could significantly decrease the levels of MRP1, P-gp, Beclin-1 and LC3II, decrease the level of HCG11 and increase the expression of miR-539-3p in HepG-2/DDP cells (P<0.01). Compared with the control group, the relative expression level of HCG11, IC50 (cisplatin), Beclin-1 and LC3II/LC3I in HCG11siRNA group decreased significantly, while the level of miR-539-3p and inhibition rate (cisplatin) increased significantly (P<0.01). Compared with PCP group, the relative expression level of HCG11 in PCP+pcDNA3.1-HCG11 group increased significantly, while the ratio of Belin-1 and LC3 II/LC3 I increased significantly (P<0.01). Compared with PCP group, the inhibition rate of PCP+pcDNA3.1+HCG11 group was significantly decreased under different concentrations of cisplatin (P<0.01). Compared with PCP group, tumor volume and tumor weight in PCP+HCG11shRNA group were significantly decreased, and the levels of Belin-1 and LC3II/LC3I were significantly decreased (P<0.05). Conclusion: PCP can affect the proliferation of hepatocellular carcinoma cells by regulating drug resistance and autophagy through LncRNA HCG11/miR-539-3p.